'Original sin' suspicion, institutional environment, and corporate philanthropy in private enterprises. Issue 1 (2nd January 2019) - Li, Xue; Luo, Jin-hui; Huang, Zeyue
ABSTRACT: The suspicion of 'original sin' is an unavoidable problem in the development of China's private enterprises. Using a sample of A-share private listed firms from 2004–2016, we investigate whether and how the suspicion of 'original sin' of private enterprises affects their corporate philanthropy. We find that private enterprises with the suspicion of 'original sin' have stronger incentives to take corporate philanthropy as a strategic tool to reduce the threat arising from the 'original sin'. High development levels of institutional environment can attenuate the positive effect of 'original sin' suspicion on private enterprises' corporate philanthropy. Furthermore, we find that the positive association between the 'original sin' suspicion of private enterprises and their corporate philanthropy is more pronounced when they do not have political connections and/or after their ultimate controllers are showed up on the Hurun Rich List.